PERANCANGAN DESYGN SYGN SYSTEM PASAR TRADISIONAL MARISA - Risti Puspita Sari Hunowu; Siska Udilawaty (UNIVERSITAS STEKOM, 2023)
The need for a sign system at the Marisa traditional market will make it easier for visitors to get information. Designing a sign system in an attractive, effective, informative and communicative market area will be the right solution. The purpose of the design is to make it easier for visitors to recognize the shopping flow and layout of the Marisa Traditional Market. This study uses a design method with a qualitative approach as a technique in collecting data. The design method is intended to produce a product in the form of a Marisa Traditional Market sign system design. While the qualitative approach is used as a way to find and collect data from the field. The data were then identified and analyzed descriptively using 5 W + 1 H so that it gave birth to a sign system design concept for the Marisa traditional market. Next, the concept is visualized until it becomes the final design in the form of the Marisa Traditional Market sign system